2010
DOI: 10.1097/jto.0b013e3181e8b3c5
|View full text |Cite
|
Sign up to set email alerts
|

Complex Mutations in the Epidermal Growth Factor Receptor Gene in Non-small Cell Lung Cancer

Abstract: Complex EGFR mutations are not rare. Gefitinib has different efficacy according to the type of complex EGFR mutations. Patients with Del-19 and L858R mutations may benefit more from gefitinib than other types of complex mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
69
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 26 publications
(23 reference statements)
8
69
0
3
Order By: Relevance
“…A retrospective study which investigated the frequency of complex mutations in 783 NSCLC patients found the majority was G719S plus L858R mutation (n = 8), the result also suggested poor response to gefitinib in patients with G719S plus L858R mutation [36]. Besides, previous studies revealed that patients with exon 18 (G719S) plus L858R mutation showed poor outcomes with gefitinib [37], [38], [39].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study which investigated the frequency of complex mutations in 783 NSCLC patients found the majority was G719S plus L858R mutation (n = 8), the result also suggested poor response to gefitinib in patients with G719S plus L858R mutation [36]. Besides, previous studies revealed that patients with exon 18 (G719S) plus L858R mutation showed poor outcomes with gefitinib [37], [38], [39].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant references from the searched studies (6 references) were also reviewed. In total, 18 patients with EGFR Del-19 + L858R mutations that received EGFR-TKIs were identified between January 2002 and January 2015 (Table I) (17)(18)(19)(20)(21)(22). Of these 18, 16 patients were assessed based on RECIST (15) and 2 patients were not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…According to Wu et al (21) the mutation rate of the EGFR gene in women and men was 42.9 and 23.1%, respectively. In this study, the mutation rate in female patients was 68.42%, which was higher compared with that in male patients (37.5%), with a statistically significant difference (P<0.05) (10,18,19,21). The degree of differentiation of the tumor was an important index for assessing malignant potential and prognosis.…”
Section: Discussionmentioning
confidence: 87%
“…EGFR acts on the cell signal transduction pathway, promotes the differentiation and proliferation of tumor cells, promotes tumor angiogenesis and metastasis and inhibits apoptosis (14)(15)(16). Multiple studies have proven that customized therapy significantly improved the survival rate and life quality of EGFR-positive lung cancer patients (17,18). With the improved understanding of the process of tumor pathogenesis and of the effects of EGFR gene mutation on tumor characteristics, targeted therapy has become increasingly more important, perfected and normalized (15).…”
Section: Discussionmentioning
confidence: 99%